Determining Factors that Influence Heart Hate Recovery (HRR) Result on Treadmill Stress Test - F Rahman (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Introduction: Stress exercise electrocardiogram is a valid diagnostic and prognostic tool for .....